Motivational Rehabilitation using Serious Games - Antoni Jaume i Capó; Javier Varona Gómez; Gabriel Moyà; Francisco Perales (Virtual Archaeology Review, 2013)
Research studies show that serious games help to motivate users in rehabilitation processes, and rehabilitation results are better when users are motivated. In long term rehabilitation for maintaining capacities, the demotivation of chronic patients is common. In this work, we have implemented balance rehabilitation video game for cerebral palsy patients. The video game was developed using the prototype development paradigm and following desirable features for rehabilitation serious games presented in the literature. We have tested the video game with a set of users who abandoned therapy due to demotivation in the previous year. Results show that the set of users improved their balance and motivation.